COMPARABLE DEVELOPMENTAL COMPETENCE OF IN VITRO FERTILIZED AND PARTHENOGENETICALLY ACTIVATED OVINE EMBRYOS - RAJA, S; BALASUBRAMANIA, S; DHINAKAR RAJ, G; VEERAPANDIAN, C (The Indian Journal of Animal Reproduction, 2015)
The present research throws light on utilizing parthenogenetically activated (PA) embryos instead of in vitro fertilized (IVF) embryos because the developmental rates of 2-, 4-, 8-16 cell and morula stages were similar (p>0.05) between IVF and PA embryos of sheep.